ANALISIS PERHITUNGAN PPh PASAL 21 ATAS TUNJANGAN HARI RAYA KARYAWAN PADA PT. WAHANA POTENSI GUNA PALEMBANG - Rosnani Assik (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
The purpose of this research is to find out the amount of tax calculation regarding income tax article 21 on holiday allowances at PT. Potential Vehicle for Palembang. The problem that is taken and raised in this study is how the relationship between the calculation of Income Tax Article 21 on holiday allowances received by employees at PT. Wahana Potensi Guna Palembang, how much is the tax payable calculation regarding the calculation of Income Tax Article 21 on holiday allowances received by employees of PT. Wahana Potensi Guna Palembang and financial reporting analysis on the calculation of income tax article 21 on holiday allowances received by employees at PT. Potential Vehicle for Palembang. In this study, the variables used are independent variables in the form of salaries, honoraria and other payments of any name in connection with work, services or activities carried out by individual domestic taxpayers. The population and from this study are employees of PT. Potential Vehicle for Palembang, totaling 12 people. Because the population is small, the entire population is madesample or called saturated sample. The results showed that PT. Wahana Potensi Guna Palembang has not calculated the holiday allowances into tax calculations because the company considers holiday allowances not included in company expenses. The holiday allowance is not included as a taxpayer's income in the calculation of income tax article 21, as a result, the company does not provide for the deduction of income tax article 21 for employees. The total calculation of income tax article 21 on the main benefit is Rp. 3,007,226.00 from the results of calculations based on holiday allowances for employees of PT. Potential Vehicle for Palembang.